Aneuploidy Detection in Pigs Using Comparative Genomic Hybridization: From the Oocytes to Blastocysts - Hornak, Miroslav; Oracova, Eva; Hulinska, Pavlina; Urbankova, Leona; Rubes, Jiri (PLOS ONE, 2012)
Data on the frequency of aneuploidy in farm animals are lacking and there is the need for a reliable technique which is capable of detecting all chromosomes simultaneously in a single cell. With the employment of comparative genomic hybridization coupled with the whole genome amplification technique, this study brings new information regarding the aneuploidy of individual chromosomes in pigs. Focus is directed on in vivo porcine blastocysts and late morulas, 4.7% of which were found to carry chromosomal abnormality. Further, ploidy abnormalities were examined using FISH in a sample of porcine embryos. True polyploidy was relatively rare (1.6%), whilst mixoploidy was presented in 46.8% of embryos, however it was restricted to only a small number of cells per embryo. The combined data indicates that aneuploidy is not a prevalent cause of embryo mortality in pigs.